Customary Law of Exchanging Rings During Proposal (Khitbah) in Ds. Sidorejo, Saradan District, Madiun Regency: The Perspective of Ulama' Madzhab Shafi'i - Fauzi, Mahfud; Syafi'i, Ahmad; Ayu, Diyan Putri (Rechtsvinding, 2024)
The tradition of exchanging rings during a proposal (khitbah) is still widely practiced in Sidorejo Village, Saradan District, Madiun Regency. In this tradition, the bride and groom put on rings, and the groom wears a gold ring without considering clear laws. Some people believe that this tradition is a sign that the woman has been proposed to and the man has proposed, in addition to following the development of the times. This study uses a qualitative descriptive method to analyze the law of exchanging rings from the perspective of the Syafi'i School. According to Syafi'i scholars, if the ring is made of gold, it is haram for men because there is a hadith that prohibits the use of silk and gold for men, even though the gold content is small. In conclusion, the tradition of exchanging rings in Sidorejo Village is carried out as part of the community's customs, but the practice of wearing gold rings for men is considered haram according to the Syafi'i School.